Testen der Tester? Grundsätze ordnungsgemäßen Testens! - Andreas Oehler (Wirtschaftsdienst, 2014)
Tests und Vergleiche von Gütern und Dienstleistungen sind mittlerweile weit verbreitet. Würde der einzelne Verbraucher den Vergleich selbst durchführen, wäre dies mit hohen Kosten verbunden, institutionelle Tests bieten demgegenüber eine gute Informationsmöglichkeit. Die Vertrauenswürdigkeit der Tester ist dabei von herausragender Bedeutung. Der Autor stellt Grundsätze für ordnungsgemäßes Testen auf und schlägt vor, wie diese kontrolliert werden können. – – Tests and comparisons of products can provide useful information on both quality and value of goods and services for consumers, suppliers, and for consumer policy, for example watchdogs. In a market economy like Germany, where consumer markets are not fully transparent and functioning, testing organisations act as information intermediaries. They provide information at the meta-level so that not everyone has to test and compare all goods and services individually. This is why the reliability of testers and testing organisations is of particular importance. This article examines the principles or minimum standards for proper testing and discusses how to control them.
Keywords: D11; D18; K2; 330